High-reliability friction material for electromagnetic brake and preparation method thereof
By using reinforcement materials such as modified basalt fibers and PBO fibers in electromagnetic brakes, combining adhesives such as benzoxazine and phenolic resins, as well as fillers such as barite and scale graphite, the friction materials are made in high temperature and high humidity environments. The problem of driving torque attenuation achieves more stable braking performance and lower wear rate.
Patent Information
- Application Number
- CN202411520808.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
After the existing friction materials are run for a long time without load in high temperature and high humidity environment, the brake torque may be attenuated, and the brake may slip when braking is required, which has the risk of braking force attenuation.
A high-reliability friction material for electromagnetic brakes is used, and the raw materials include adhesives, reinforcement materials, friction enhancing fillers and friction reducing fillers. Specific compositions include benzoxazine, phenolic resin, nitrile glue powder as adhesives, modified basalt fibers, PBO pulp, ceramic fibers, etc. as reinforcement materials, barite, scale graphite, etc. as friction enhancement and friction reduction fillers . The surface roughness and bonding properties of the fiber are enhanced by the modification treatment and modified basalt fibers with silane coupling agent.
It improves the high temperature, humidity and wear resistance of friction materials, reduces the attenuation of braking torque, reduces the risk of brake slippage, and improves the stability of braking performance.
Smart Images

Figure BDA0005108000120000111 
Figure BDA0005108000120000131 
Figure BDA0005108000120000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of friction materials, in particular to a friction material for a high-reliability electromagnetic brake and a preparation method thereof. Background Art
[0002] Electromagnetic brakes are widely used in areas that require braking control, such as servo motors, robots, forklifts, and aerial work vehicles, especially in areas that require precision control, such as robots and mechanical control arms. During operation, the friction plate rotor and the motor spindle keep rotating, and braking is only performed when braking is required. While the friction plate rotor keeps rotating, the friction plate inevitably contacts the mating part and generates heat. If the brake remains idle for a long time and is in a hot and humid environment, and the brake rotor is in a sealed state, the heat is difficult to dissipate quickly, which will cause the friction coefficient of the friction plate to decline, causing the brake to slip when braking is required, and there is a risk of braking force attenuation. Therefore, the development of a friction material for electromagnetic brakes suitable for high temperature and high humidity environments is of great significance to solving the problem of electromagnetic brake braking torque attenuation after long-term operation in high temperature and high humidity environments. Summary of the invention
[0003] Technical problems solved by the present invention:
[0004] It is used to solve the problem of torque attenuation of the current friction material after long-term no-load operation in a high temperature and high humidity environment, improve the stability of the brake performance, and reduce the brake slippage caused by the attenuation of the braking torque.
[0005] The technical solution adopted by the present invention is:
[0006] In view of the above technical problems, an object of the present invention is to provide a friction material for an electromagnetic brake with high reliability and a preparation method thereof.
[0007] The specific contents are as follows:
[0008] First, the present invention provides a friction material for a high-reliability electromagnetic brake, wherein the raw material components include an adhesive, a reinforcing material, a friction-increasing filler, and a friction-reducing filler;
[0009] Adhesives include benzoxazine, phenolic resin, and nitrile rubber powder;
[0010] Reinforcement materials include modified basalt fiber, PBO pulp, ceramic fiber, plant fiber, carbon fiber powder, potassium titanate platelets;
[0011] Friction-increasing fillers include barite, light calcium carbonate, friction particles, wollastonite powder, aluminum titanium powder, feldspar powder, alumina, zircon powder, and garnet powder;
[0012] Anti-friction fillers include flake graphite, artificial graphite, flexible graphite, composite metal sulfide, and polymer lubricating material powder.
[0013] Modified basalt fiber is obtained by removing impurities from basalt, putting it into a modification solution, and then treating it with a silane coupling agent; impurity removal treatment: vacuum heat treatment at 500-600℃ for 0.5-2h; modification solution: V 双氧水 :V 饱和氨水 :V 饱和氢氧化钙 =1:1:1. Modification treatment: soak at 40-70℃ for 18-36h; silane coupling agent is KH-550, and the silane coupling agent is configured into a solution, V 硅烷偶联剂 :V 水 :V 乙醇 =5~15:60~80:10~30. The modified basalt fiber is used to make its surface rougher and have stronger grip on the material. After being modified with alkali solution, the defects and holes on the fiber surface will be eroded, the remaining fiber surface will become rough, and the fiber strength will also be enhanced. A large number of active groups will be generated on the surface of the basalt fiber modified by silane coupling agent, which greatly enhances the bonding performance of the resin, improves the bonding strength, and then improves the high temperature resistance of the resin matrix.
[0014] Composite metal sulfide: zinc sulfide, tin sulfide, ferrous sulfide, the mass ratio of the three is 4-6:3-4:1-2. More preferably, the mass ratio of the three is 5:3:2.
[0015] According to some preferred embodiments, the raw material components are measured by weight, including 2 to 5 parts of benzoxazine, 3 to 6 parts of phenolic resin, 2 to 5 parts of nitrile rubber powder, 2 to 5 parts of modified basalt fiber, 1 to 3 parts of PBO pulp, 10 to 15 parts of ceramic fiber, 2 to 5 parts of plant fiber, 1 to 3 parts of carbon fiber powder, 6 to 10 parts of potassium titanate platelets, 5 to 10 parts of barite, 5 to 10 parts of light calcium carbonate, 10 to 20 parts of friction particles, 10 to 14 parts of wollastonite powder, 5 to 10 parts of aluminum titanium powder, 6 to 10 parts of feldspar powder, 1 to 3 parts of alumina, 1 to 3 parts of zircon powder, 4 to 6 parts of garnet powder, 2 to 4 parts of flake graphite, 2 to 4 parts of artificial graphite, 5 to 8 parts of flexible graphite, 3 to 5 parts of composite metal sulfide, and 0.5 to 2 parts of polymer lubricating material powder.
[0016] According to some more preferred implementation methods, the components of the raw materials are, by weight, combination one, combination two or combination three;
[0017] Combination 1: 3 parts of benzoxazine, 4 parts of phenolic resin, 3 parts of nitrile rubber powder, 3 parts of modified basalt fiber, 3 parts of PBO pulp, 14 parts of ceramic fiber, 3 parts of plant fiber, 2 parts of carbon fiber powder, 8 parts of potassium titanate platelets, 8 parts of barite, 5 parts of light calcium carbonate, 14 parts of friction particles, 14 parts of wollastonite powder, 8 parts of aluminum titanium powder, 6 parts of feldspar powder, 2 parts of alumina, 1 part of zircon powder, 5 parts of garnet powder, 8 parts of flake graphite, 2 parts of artificial graphite, 8 parts of flexible graphite, 3 parts of composite metal sulfide, 1 part of polymer lubricating material powder;
[0018] Combination 2: 2 parts of benzoxazine, 6 parts of phenolic resin, 4 parts of nitrile rubber powder, 2 parts of modified basalt fiber, 2 parts of PBO pulp, 10 parts of ceramic fiber, 5 parts of plant fiber, 2 parts of carbon fiber powder, 9 parts of potassium titanate platelets, 9 parts of barite, 10 parts of light calcium carbonate, 18 parts of friction particles, 10 parts of wollastonite powder, 5 parts of aluminum titanium powder, 8 parts of feldspar powder, 1 part of alumina, 3 parts of zircon powder, 4 parts of garnet powder, 6 parts of flake graphite, 3 parts of artificial graphite, 6 parts of flexible graphite, 4 parts of composite metal sulfide, 0.5 parts of polymer lubricating material powder;
[0019] Combination three: 4 parts of benzoxazine, 3 parts of phenolic resin, 2 parts of nitrile rubber powder, 4 parts of modified basalt fiber, 1 part of PBO pulp, 12 parts of ceramic fiber, 4 parts of plant fiber, 3 parts of carbon fiber powder, 6 parts of potassium titanate platelets, 5 parts of barite, 8 parts of light calcium carbonate, 12 parts of friction particles, 12 parts of wollastonite powder, 6 parts of aluminum titanium powder, 10 parts of feldspar powder, 3 parts of alumina, 2 parts of zircon powder, 6 parts of garnet powder, 5 parts of flake graphite, 4 parts of artificial graphite, 5 parts of flexible graphite, 5 parts of composite metal sulfide, and 1.5 parts of polymer lubricating material powder.
[0020] According to some preferred embodiments, in the adhesive: the particle size of the benzoxazine resin is 200 mesh; the particle size of the phenolic resin is 200 mesh; and the particle size of the nitrile rubber powder is 40 mesh.
[0021] According to some preferred embodiments, among the components of the reinforcing material, according to the different length ratios of the materials, the materials with a length greater than 1 mm account for 10-20% of the total weight, the materials with a length of 0.2-1 mm account for 40-60% of the total weight, and the materials with a length less than 0.2 mm account for 20-30% of the total weight; the plant fiber includes at least one of sisal fiber, bamboo fiber, flax fiber, and coconut shell fiber; the basalt fiber is 1-2 mm long; the PBO pulp is 1-1.4 mm long; the plant fiber is 0.4-0.7 mm long; the ceramic fiber is 0.3-0.5 mm long; the carbon fiber powder is 200 mesh; the length and width of the potassium magnesium titanate platelets are both 0.5-5 μm, and the thickness is 0.2-1.5 μm.
[0022] According to some preferred embodiments, among the components of the friction-increasing material, according to the different particle size ratios of the materials, the materials with a particle size of less than 16 mesh account for 15-30% of the total weight, the materials with a particle size of 40 mesh to 100 mesh account for 10-20% of the total weight, and the materials with a particle size of more than 100 mesh account for 50-75% of the total weight; the Mohs hardness of barite is 3, 325 mesh; the Mohs hardness of light calcium carbonate is 3, 325 mesh; the friction particles have a Mohs hardness of 3-4 and a particle size of 16 mesh; wollastonite Mohs hardness of powder is 5, 325 mesh; Mohs hardness of aluminum titanium powder is 5, 400 mesh; Mohs hardness of feldspar powder is 6, 325 mesh; Mohs hardness of alumina is 7, 325 mesh; Mohs hardness of zircon powder is 7, 325 mesh; Mohs hardness of garnet powder is 7, 325 mesh; among the components of the friction-increasing material: fillers with Mohs hardness of 3 to 6 are room temperature friction-increasing fillers, accounting for 80 to 90wt%; fillers with Mohs hardness above 7 are high temperature friction-increasing fillers, accounting for 10 to 20wt%.
[0023] According to some preferred embodiments, in the friction-reducing material, flake graphite is 100 mesh; artificial graphite is 40-60 mesh; flexible graphite is 40-60 mesh; composite metal sulfide is 325 mesh; polymer lubricating material powder is 600 mesh.
[0024] Second, the present invention provides a method for preparing the friction material for the above-mentioned high-reliability electromagnetic brake, comprising the following steps:
[0025] S1 weighs the raw materials in proportion and pours them into the mixing equipment in the order of density from small to large;
[0026] S2 Drying of the molded material after mixing;
[0027] S3 is dried and pressed into a mold to obtain a semi-finished product;
[0028] S4 performs gradient temperature increasing treatment to obtain the friction material;
[0029] S5 friction material is surface ground;
[0030] S6 surface treatment was followed by surface ablation.
[0031] Specifically, it means:
[0032] S1 Mixing: Weigh the raw materials of each component in proportion, and pour them into the plowshare mixer in the order of density from small to large for blending. The main shaft speed of the mixer is 200-300r / min, and the reamer speed is 2000-3000r / min.
[0033] S2 Drying: Dry the mixed molding material in an oven at 80°C for 2 to 3 hours.
[0034] S3 hot pressing: Use 100T four-column hydraulic press to evenly spread the dried molding material into the mold for pressing. The pressing temperature is 170±5℃, the pressing pressure is 20~40MPa, and the pressure is maintained for 60~80s / mm. Exhaust gas is carried out before pressure maintenance. Press for 20s, exhaust gas for 2s, and enter the pressure maintenance stage after two exhaust gas treatments. After the pressure maintenance, the semi-finished friction material is obtained.
[0035] S4 heat treatment: heat from room temperature to 140℃ over 1h, keep warm for 1-2h, heat from 140℃ to 160℃ over 30min, keep warm for 2-3h, heat from 160℃ to 190℃ over 30min, keep warm for 1-2h, heat from 190℃ to 210℃ over 30min, keep warm for 3-4h, then cool to 50℃ and take out.
[0036] S5 Grinding: Grind the heat-treated friction material through a double-end belt grinder to remove surface oxide scale, burrs and flash.
[0037] S6 ablation: After cleaning and drying, the ground friction plate is subjected to surface ablation treatment. The ablation temperature is 500-700°C and the ablation time is 20-60s.
[0038] The beneficial effects achieved by the present invention are:
[0039] (1) The reinforcing material (PBO fiber pulp, modified basalt fiber, carbon fiber powder, ceramic fiber, potassium magnesium titanate platelets, plant fiber) provided by the present invention is used as the skeleton material of the friction material. The composition is: a network reinforcement system with long fiber material as the main skeleton, medium-length fiber bridging, and short fiber local reinforcement. The network reinforcement system constructed above not only has the advantages brought by the reinforcing material itself, such as friction increase, high temperature resistance, high strength, etc., but also can hinder the expansion of the matrix crack tip, thereby improving the impact strength of the friction material resin matrix.
[0040] To expand on this, it means:
[0041] First, the PBO fiber pulp and modified basalt fiber work synergistically, that is, the two fibers are close in length. During the mixing process, the rough surface of the modified basalt fiber and the fibrillated and curled PBO fiber pulp grab and entangle with each other, which increases the difficulty of pulling the fiber out of the resin matrix, thereby improving the wear resistance of the friction material.
[0042] Secondly, basalt fiber is very hard and may scratch the counterpart, but it can increase the friction coefficient of the friction material. PBO fiber is soft and when mixed with basalt fiber, it can achieve a combination of hardness and softness, which can increase friction and reduce wear rate.
[0043] Third, PBO fiber has good high temperature resistance and can be used for a long time in an environment of 600°C without performance degradation or damage. The operating temperature of basalt fiber is as high as 600°C. The mixture of PBO fiber and modified basalt fiber can significantly improve the high temperature resistance of the grinding material skeleton.
[0044] Fourthly, basalt fiber and PBO fiber pulp are grasped and entangled with a certain distance in between, while shorter ceramic fibers and plant fibers are between the overlapping long fiber distances, so that the long fibers and shorter fibers form a bridge structure, and carbon fiber powder and potassium magnesium titanate platelets can further fill the gaps between the long fibers, thereby improving the overall heat resistance and strength of the friction material and playing an auxiliary reinforcement role.
[0045] Fifth, the small particle size of carbon fiber powder can hinder the expansion of the matrix crack tip, thereby improving the impact strength of the friction material resin matrix.
[0046] Sixth, carbon fiber powder has a "turbulent graphite" structure, showing good self-lubrication and friction reduction properties, which can improve the wear resistance of friction materials. Plant fibers have strong adsorption properties for powders, which can improve the dispersion of the mixture and enhance the overall consistency of the resin matrix.
[0047] Seventh, in the prior art, for example, publication number CN115612243A discloses the use of a combination of basalt fiber, steel fiber and carbon fiber, wherein the steel fiber and carbon fiber can fill the gaps in the basalt fiber. However, steel fiber is prone to rust in a hot and humid environment, causing the friction plate and the mating part to rust and stick, and the steel fiber is prone to scratching the mating part, generating noise. In the present invention, basalt fiber is an inorganic fiber that will not rust and has very good high-temperature creep resistance. Basalt fiber is blended with PBO fiber to improve the high-temperature creep resistance of the friction material, and works together with benzoxazine resin and phenolic resin matrix to improve the high-temperature dimensional stability of the friction material.
[0048] (2) The adhesive (phenolic resin, benzoxazine and nitrile rubber powder) provided by the present invention can reduce the high temperature decay of the friction material and improve the moisture resistance of the friction material through the combination of adhesive components, making it suitable for humid environments. It can also improve the impact strength of the substrate and the compressibility of the friction material, increase the fit between the friction material and the mating surface, and improve the initial friction coefficient. In detail, that is to say:
[0049] First, the curing temperature of benzoxazine is about 200°C, and the curing temperature of phenolic resin is 150-170°C. Mixing benzoxazine and phenolic resin can further reduce the curing temperature of the system, and reduce the curing temperature of the bonding system to about 170°C. This is because the presence of phenolic hydroxyl groups and ortho- and para-active hydrogen in phenolic resin promotes the opening of the oxazine ring, allowing it to react at a lower temperature. The released heat promotes the condensation reaction of phenolic resin, improves production efficiency, and reduces energy consumption.
[0050] Secondly, benzoxazine has very good fluidity and can be self-leveling at 120°C. Blending with phenolic resin improves the fluidity of the pressed plastic, reduces the content of adhesive, further reduces the high-temperature decay of the friction material, and also reduces material costs.
[0051] Third, benzoxazine is a high-temperature resistant thermosetting resin with a long-term use temperature of about 300°C, while the long-term use temperature of phenolic resin is 200°C. Phenolic resin and benzoxazine are blended to form a cross-penetrating network structure, which can increase the thermal decomposition temperature of the resin matrix and thereby reduce the thermal decay of the friction material.
[0052] Fourthly, benzoxazine is a ring-opening polymer resin that can surround and isolate a large number of phenolic hydroxyl groups of phenolic resin, while reducing the rigid structure content of methylene-benzene ring-methylene, which is beneficial to the chemical stability and mechanical properties of the blended resin after curing. No small molecules are released during the polymerization process, which can reduce the number of hot pressing exhaust times, reduce defects such as blistering and delamination, reduce scrap rate, and improve production efficiency. The volume of benzoxazine is close to zero shrinkage when it is cured, which is convenient for mold design.
[0053] Fifth, benzoxazine has low water absorption, which is lower than that of phenolic resin and epoxy resin. Therefore, the friction material with benzoxazine as a binder has better water resistance and is suitable for humid environments. Benzoxazine and phenolic resin are blended to improve the high temperature resistance of the resin system, improve the fluidity of the system, and improve the production processability.
[0054] Sixth, the nitrile rubber powder and the resin matrix form a "sea-island" structure. When the rubber is impacted, the silver streaks can absorb the impact energy and increase the impact strength of the matrix. It can also increase the compressibility of the friction material, increase the fit between the friction material and the mating surface, and increase the initial friction coefficient.
[0055] (3) The friction material provided by the present invention adopts a coarse, medium and fine combination to form a similar "suspended-dense" structure, that is, the materials exist continuously from large to small, the number of coarse particles is small and the fine aggregate is large, and the coarse particles exist in a suspended state between the fine particles, forming a high-density and high-strength structure; the formed structure makes the matrix have good stability and durability. The friction particles provided by the present invention (Shijiazhuang Shuoruo Technology Co., Ltd., TKL-01-P / GJ) are a semi-cured mixture of resin and inorganic matter, and have a high heat resistance temperature. Particles with large particle size can reduce the total surface area of the filler, and then reduce the surface area of the resin infiltration, so as to further reduce the amount of resin, that is, to reduce the risk of thermal decay of the friction material. At the same time, the friction particles have a certain elasticity, and can produce a certain amount of deformation during pressing, so that the friction material is pressed more densely and the porosity of the friction material is reduced. After the pressure is released, the friction particles have a certain resilience, which can improve the compressibility of the friction material. The presence of friction particles can further conduct the impact force generated during braking to the inside of the friction material, reduce the heat generated by the braking energy on the surface of the friction material, avoid excessive temperature rise on the surface of the friction material, and make the friction coefficient of the friction material stable at high temperatures and reduce thermal decay. Garnet is dark red in color, has high hardness, high density, good toughness, good high temperature resistance, sharp corners and sharp edges, which can increase the tangential force of the contact surface of the friction material, thereby increasing the friction coefficient of the friction material. The use of garnet powder can stabilize the friction coefficient, reduce the wear rate, and reduce the generation of noise.
[0056] (4) The friction-increasing filler provided by the present invention adopts fillers with different Mohs hardnesses to be mixed, which can increase the friction coefficient at each temperature stage while reducing the wear of the friction material, thereby extending the service life of the friction material. In detail, that is to say:
[0057] A high proportion of fillers with a Mohs hardness of 3 to 6 enables the friction material to have a better friction-increasing effect at a lower temperature, and a low proportion of friction-increasing materials with a Mohs hardness of 6 or more has a higher friction coefficient at a higher temperature. Since fillers with a Mohs hardness of 6 or more are high-hardness fillers, excessive use will scratch the pair and increase the wear of the friction material. Therefore, the present invention increases the friction coefficient at each temperature stage and reduces the wear of the friction material through the use of a certain proportion, thereby extending the service life of the friction material.
[0058] (5) The anti-friction filler (flake graphite, artificial graphite, flexible graphite, composite metal sulfide, polymer lubricating material) provided by the present invention has good lubricity, thereby reducing the wear of the friction material and improving the stability of the friction material in a high temperature and high humidity environment. In detail, that is to say:
[0059] Flake graphite can reduce low-temperature wear of friction materials, artificial graphite can reduce medium- and low-temperature wear of friction materials, and composite metal sulfides can reduce high-temperature wear of friction materials. Flexible graphite can increase the flexibility of friction materials and also has a certain friction reduction effect. Polymer lubricating materials have good lubricity and can fill the pits formed by the shedding of friction surface particles, further reducing the wear of friction materials. In addition, polymer lubricating materials and benzoxazine work synergistically, and polymer lubricating materials form a thin film covering the resin matrix, further preventing moisture from penetrating into the resin matrix, and improving the stability of friction materials in high temperature and high humidity environments. Polymer lubricating materials have good anti-sticking properties and can also reduce the risk of adhesion between friction materials and mating parts.
[0060] (6) In the preparation method provided by the present invention, the organic matter content on the surface of the friction material is reduced by an ablation process, the internal structure of the friction material is optimized during high-temperature ablation, and the thermal decay resistance is greatly improved. The friction material is a multi-component composite material composed of an adhesive, a reinforcing material and a filler, similar to a sea-island structure. The adhesive is seawater, and the reinforcing filler and the filler are equivalent to the island. Through ablation, the adhesive, plant fiber and other parts on the surface are partially vaporized, volatilized and carbonized, and the harmful gases and impurities inside the material are discharged, generating fine cracks and pores, exposing the material that truly plays a role in friction, reducing the running-in time of the friction material, and reducing the thermal decay caused by carbonization on the surface of the friction material under high temperature conditions. DETAILED DESCRIPTION
[0061] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0062] Examples 1-3
[0063] The method for preparing a friction material for a high-reliability electromagnetic brake provided in the embodiment comprises the following steps:
[0064] (1) Mixing: Weigh the raw materials of each component in proportion. The proportion of each raw material component is shown in Table 1. Pour the raw materials of each component into the plowshare mixer in the order of density from small to large for blending. The main shaft speed of the mixer is 200-300r / min, and the reamer speed is 2000-3000r / min.
[0065] (2) Drying: Dry the mixed molding material in an oven at 80°C for 2 to 3 hours.
[0066] (3) Hot pressing: Use a 100T four-column hydraulic press to evenly spread the dried molding material into the mold for pressing. The pressing temperature is 170±5℃, the pressing pressure is 20-40MPa, and the pressure is maintained for 60-80s / mm. Exhaust gas is performed before pressure maintenance. Press for 20s and exhaust gas for 2s. After exhaust gas is performed twice, the pressure maintenance stage begins. After the pressure maintenance, the semi-finished friction material is obtained.
[0067] (4) Heat treatment: heat from room temperature to 140°C over 1 h, keep warm for 1-2 h, heat from 140°C to 160°C over 30 min, keep warm for 2-3 h, heat from 160°C to 190°C over 30 min, keep warm for 1-2 h, heat from 190°C to 210°C over 30 min, keep warm for 4-6 h, then cool to 50°C and take out.
[0068] (5) Rough grinding: Roughly grind the heat-treated friction material to remove surface oxide scale, burrs and flash.
[0069] (6) Ablation: After cleaning and drying, the roughly ground friction plate is subjected to surface ablation treatment. The ablation temperature is 500-600°C and the ablation time is 20-60s.
[0070] (7) Fine grinding: Fine grinding is performed on the friction plate after ablation treatment to obtain a finished friction plate.
[0071] Table 1 Distribution ratio of each group of raw materials (Example-A)
[0072]
[0073] In Table 1: Modified basalt fiber: calcine the basalt fiber in a vacuum at 500-600℃ for 1h to remove impurities such as organic matter on the surface. Soak the calcined basalt fiber in the modified solution for 24h at a temperature of 50℃. The modified solution is a mixture of hydrogen peroxide, saturated ammonia water, and saturated calcium hydroxide solution in a volume ratio of 1:1:1. After soaking, rinse the basalt fiber with distilled water. Then soak the rinsed basalt fiber in KH550 solution (the volume ratio of KH550 solution is water: ethanol: silane = 10:70:20) for 24h, then take it out and dry it at 120℃ for 1h.
[0074] Composite metal sulfide: zinc sulfide, tin sulfide, ferrous sulfide, the mass ratio of the three is 5:3:2.
[0075] The plant fiber is flax fiber.
[0076] The polymer lubricating material powder is polytetrafluoroethylene.
[0077] Comparative Examples 1-6
[0078] The raw materials of the raw materials of the comparative examples are shown in Table 2, and the preparation method is the same as that of the embodiment. Among them, comparative examples 4-6 were not subjected to ablation treatment.
[0079] Table 2 Ratio of each component of raw materials (Comparative Example-B)
[0080]
[0081] Test example
[0082] The examples and comparative examples were used as test samples, processed into rotors, and assembled on brakes for testing. The brake specifications are Z079-C12 (48V20) 32G, rated torque 32N·m, rated speed less than 1400r / min, ambient humidity 85%, ambient temperature 40°C. The brake was installed on the test bench and operated at 1400r / min without load. The brake torque was tested every 5 days, and the test was stopped when the brake slipped. The test results are shown in Table 3-4.
[0083] Table 3 Test results (Example-A)
[0084]
[0085] Table 4 Test results (Comparative Example-B)
[0086]
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A friction material for a high-reliability electromagnetic brake, characterized in that: The raw material components include adhesive, reinforcing material, friction-increasing filler, and friction-reducing filler; Adhesives include benzoxazine, phenolic resin, and nitrile rubber powder; Reinforcement materials include modified basalt fiber, PBO pulp, ceramic fiber, plant fiber, carbon fiber powder, potassium titanate platelets; Friction-increasing fillers include barite, light calcium carbonate, friction particles, wollastonite powder, aluminum titanium powder, feldspar powder, alumina, zircon powder, and garnet powder; Anti-friction fillers include flake graphite, artificial graphite, flexible graphite, composite metal sulfide, and polymer lubricating material powder.
2. The high-reliability friction material for electromagnetic brake according to claim 1, characterized in that: The components of the raw materials are calculated by weight. 2-5 parts of benzoxazine, 3-6 parts of phenolic resin, 2-5 parts of nitrile rubber powder, 2-5 parts of modified basalt fiber, 1-3 parts of PBO pulp, 10-15 parts of ceramic fiber, 2-5 parts of plant fiber, 1-3 parts of carbon fiber powder, 6-10 parts of potassium titanate platelets, 5-10 parts of barite, 5-10 parts of light calcium carbonate, 10-20 parts of friction particles, 10-14 parts of wollastonite powder, 5-10 parts of aluminum titanium powder, 6-10 parts of feldspar powder, 1-3 parts of alumina, 1-3 parts of zircon powder, 4-6 parts of garnet powder, 2-4 parts of flake graphite, 2-4 parts of artificial graphite, 5-8 parts of flexible graphite, 3-5 parts of composite metal sulfide, and 0.5-2 parts of polymer lubricating material powder.
3. The high-reliability friction material for electromagnetic brake according to claim 2, characterized in that: The components of the raw materials are calculated by weight and are combination one, combination two or combination three; Combination 1: 3 parts of benzoxazine, 4 parts of phenolic resin, 3 parts of nitrile rubber powder, 3 parts of modified basalt fiber, 3 parts of PBO pulp, 14 parts of ceramic fiber, 3 parts of plant fiber, 2 parts of carbon fiber powder, 8 parts of potassium titanate platelets, 8 parts of barite, 5 parts of light calcium carbonate, 14 parts of friction particles, 14 parts of wollastonite powder, 8 parts of aluminum titanium powder, 6 parts of feldspar powder, 2 parts of alumina, 1 part of zircon powder, 5 parts of garnet powder, 8 parts of flake graphite, 2 parts of artificial graphite, 8 parts of flexible graphite, 3 parts of composite metal sulfide, 1 part of polymer lubricating material powder; Combination 2: 2 parts of benzoxazine, 6 parts of phenolic resin, 4 parts of nitrile rubber powder, 2 parts of modified basalt fiber, 2 parts of PBO pulp, 10 parts of ceramic fiber, 5 parts of plant fiber, 2 parts of carbon fiber powder, 9 parts of potassium titanate platelets, 9 parts of barite, 10 parts of light calcium carbonate, 18 parts of friction particles, 10 parts of wollastonite powder, 5 parts of aluminum titanium powder, 8 parts of feldspar powder, 1 part of alumina, 3 parts of zircon powder, 4 parts of garnet powder, 6 parts of flake graphite, 3 parts of artificial graphite, 6 parts of flexible graphite, 4 parts of composite metal sulfide, 0.5 parts of polymer lubricating material powder; Combination three: 4 parts of benzoxazine, 3 parts of phenolic resin, 2 parts of nitrile rubber powder, 4 parts of modified basalt fiber, 1 part of PBO pulp, 12 parts of ceramic fiber, 4 parts of plant fiber, 3 parts of carbon fiber powder, 6 parts of potassium titanate platelets, 5 parts of barite, 8 parts of light calcium carbonate, 12 parts of friction particles, 12 parts of wollastonite powder, 6 parts of aluminum titanium powder, 10 parts of feldspar powder, 3 parts of alumina, 2 parts of zircon powder, 6 parts of garnet powder, 5 parts of flake graphite, 4 parts of artificial graphite, 5 parts of flexible graphite, 5 parts of composite metal sulfide, and 1.5 parts of polymer lubricating material powder.
4. The high-reliability friction material for electromagnetic brake according to any one of claims 1 to 3, characterized in that: The adhesive includes at least one of features (1-1) to (1-3): (1-1) The particle size of benzoxazine resin is 200 mesh; (1-2) The particle size of phenolic resin is 200 mesh; (1-3) The particle size of nitrile rubber powder is 40 mesh.
5. The friction material for a high-reliability electromagnetic brake according to any one of claims 1 to 3, characterized in that: The reinforcing material includes at least one of features (2-1) to (2-8): (2-1) Among the components of the reinforcing material, the length ratio of the materials is such that the materials with a length greater than 1 mm account for 10 to 20% of the total weight, the materials with a length of 0.2 to 1 mm account for 40 to 60% of the total weight, and the materials with a length less than 0.2 mm account for 20 to 30% of the total weight; (2-2) the plant fiber includes at least one of sisal fiber, bamboo fiber, flax fiber and coconut shell fiber; (2-3) Basalt fiber length 1~2mm; (2-4) PBO pulp length is 1 to 1.4 mm; (2-5) Plant fiber length 0.4~0.7mm; (2-6) Ceramic fiber length 0.3~0.5mm; (2-7) Carbon fiber powder 200 mesh; (2-8) The length and width of potassium magnesium titanate platelets are 0.5 to 5 μm, and the thickness is 0.2 to 1.5 μm.
6. The high-reliability friction material for electromagnetic brake according to any one of claims 1 to 3, characterized in that: The friction-increasing filler includes at least one of features (3-1) to (3-11): (3-1) Among the various components of the friction-increasing material, the materials with a particle size of less than 16 mesh account for 15 to 30% of the total weight, the materials with a particle size of 40 to 100 mesh account for 10 to 20% of the total weight, and the materials with a particle size of more than 100 mesh account for 50 to 75% of the total weight; (3-2) Barite Mohs hardness 3, 325 mesh; (3-3) Light calcium carbonate Mohs hardness 3, 325 mesh; (3-4) Friction particles with Mohs hardness of 3-4 and particle size of 16 mesh; (3-5) Wollastonite powder Mohs hardness 5, 325 mesh; (3-6) Aluminum titanium powder Mohs hardness 5, 400 mesh; (3-7) Feldspar powder Mohs hardness 6, 325 mesh; (3-8) Aluminum oxide Mohs hardness 7, 325 mesh; (3-9) Zircon powder Mohs hardness 7, 325 mesh; (3-10) Garnet powder Mohs hardness 7, 325 mesh; (3-11) Among the components of the friction-increasing material: fillers with a Mohs hardness of 3 to 6 are room-temperature friction-increasing fillers, accounting for 80 to 90 wt%; fillers with a Mohs hardness of 7 or above are high-temperature friction-increasing fillers, accounting for 10 to 20 wt%.
7. The high-reliability friction material for electromagnetic brake according to any one of claims 1 to 3, characterized in that: The anti-friction material includes at least one of features (4-1) to (4-7): (4-1) Flake graphite 100 mesh; (4-2) Artificial graphite 40-60 mesh; (4-3) Flexible graphite 40-60 mesh; (4-4) Composite metal sulfide 325 mesh; (4-5) polymer lubricating material powder 600 mesh; (4-6) The composite metal sulfide includes zinc sulfide, tin sulfide, and ferrous sulfide, and the mass ratio of the three is 4-6:3-4:1-2. (4-7) The polymer lubricating material powder includes at least one of polyetheretherketone, polytetrafluoroethylene, and ultra-high molecular weight polyethylene.
8. A method for preparing a friction material for a high-reliability electromagnetic brake according to any one of claims 1 to 7, characterized in that: The steps include: S1 weighs the raw materials in proportion and pours them into the mixing equipment in the order of density from small to large; S2 Drying of the molded material after mixing; S3 is dried and pressed into a mold to obtain a semi-finished product; S4 performs gradient temperature increasing treatment to obtain the friction material; S5 friction material is surface ground; S6 surface treatment was followed by surface ablation.
9. The method for preparing a friction material for a high-reliability electromagnetic brake according to claim 8, characterized in that: In S3, the pressing temperature is 170±5℃, the pressing pressure is 20-40MPa, and the pressure holding is performed at 60-80s / mm; and / or, in S4, the temperature is increased gradually: from room temperature to 140℃ for 1h, kept warm for 1-2h, from 140℃ to 160℃ for 30min, kept warm for 2-3h, from 160℃ to 190℃ for 30min, kept warm for 1-2h, from 190℃ to 210℃ for 30min, kept warm for 3-4h, and then taken out after furnace cooling.
10. The method for preparing a friction material for a high-reliability electromagnetic brake according to claim 8 or 9, characterized in that: In S6, the ablation temperature is 500-700° C., and the ablation time is 20-60 s.
Citation Information
Patent Citations
High-wear-resistance high-molecular material for friction plate and preparation method of high-wear-resistance high-molecular material
CN115612243A
Cited By
Preparation method of modified PBO fiber toughening agent for well cementation under high-frequency alternating injection-production condition
CN119640581A
Friction material with stable friction coefficient for electromagnetic brake and preparation method of friction material
CN119661978A
Stable-size and anti-adhesion friction material for electromagnetic brake and preparation method of friction material
CN120519009A
A dimensionally stable and anti-adhesion friction material for electromagnetic brakes and a preparation method thereof
CN120519009B